Perceptions and Food Practices of Gastronomy Students at a Brazilian Public University (Research, Society and Development, 2021)
The number of overweight and obese individuals in Brazil has increased in recent decades. Chronic Non-Communicable Diseases (NCDs) are currently the leading cause of death among adults. Balanced diet, along with other factors such as frequent physical activity and leisure, positively affect weight maintenance and prevent the onset of these diseases. Studies on the food consumption of Brazilian university under graduates observe a high incidence of food inadequacy, overweight and obesity among students. Considering characteristics that help guarantee life quality from food among students, the present study aimed to investigate nutritional perceptions and eating practices of students in the gastronomy course at a public university in Brazil. The research used as a method the cross-sectional study, in which we sought to understand the incidence of factors related to the food context during the academic experience. The observed factors were nutritional profile, food consumption and nutritional knowledge following methodologies already validated. The investigated subjects were students of both gender in the gastronomy course from the second to the eighth semester. For data collection, Google forms online questionnaires were applied, with students who fulfilled the requirements of the investigation. The results indicate a high incidence of overweight and obesity, high and medium nutritional knowledge and inadequacy in different aspects of alimentation of the sample. The results, together with the bibliographic material surveyed, revealed that the nutritional knowledge of the students, in isolation, was not a factor of positive change in eating habits and consequent weight maintenance and disease prevention.